EFFICACY OF PS-VEPS IN THE DETECTION OF SUBCLINICAL OPTIC NEURITIS FOLLOWING ETHAMBUTOL IN THERAPEUTIC DOSAGE - Satendra, Singh; Sushma, Sood; -, Beena; Shelly, Goyal (Pakistan Journal of Physiology, 2006)
Background: Ethambutol is an antimicrobial agent used frequently to treat tuberculosis. The most commonly recognized toxic effect of ethambutol is optic neuropathy, which may sometime results in irreversible vision loss. However, early recognition not only prevents this complication, it also increases compliance of the drug. This study was carried out to assess the usefulness of patternshift visual evoked potentials (PS-VEPs) in the detection of sub clinical optic neuropathy in patients on ethambutol for the treatment of tuberculosis in the recommended dosage. Methods: 30 consecutive patients of tuberculosis were studied before and after two months of ethambutol therapy. Ethambutol was administered in the WHO recommended dosage of 15mg/kg of body weight. All the patients underwent pattern shift visual evoked potential tests, which check the function of the visual pathway from the retina to the occipital cortex. Result: PS-VEP abnormalities were seen in 5 patients (16.7%),out of which prolonged latency was documented in 3 patients (10%),increased latency difference was seen in 1 patient (3.3%) and abnormal amplitude difference was reported in 1 patient (3.3%).Associated psychophysical abnormalities of visual acuity in 2 patients(6.7%) and color vision abnormality in 1 patient (3.3%) were also seen. Conclusion: Our study confirms that during the treatment with ethambutol, PS-VEPs may reveal a surprisingly high percentage of sub clinical optic neuritis even at dosages considered to be safe. This needs attention in terms of patient care and drug compliance.